2021
DOI: 10.1080/17474124.2021.1911644
|View full text |Cite
|
Sign up to set email alerts
|

Burden of comorbid anxiety and depression in patients with inflammatory bowel disease: a systematic literature review

Abstract: Introduction Patients with inflammatory bowel disease (IBD), including Crohn's disease and ulcerative colitis, often have comorbid anxiety and depression that affects their quality of life (QoL) and management of their IBD. Areas covered A systematic literature review (SLR) was conducted to identify articles and conference abstracts on comorbid anxiety and depression in IBD patients using MEDLINE ® and Embase ® (January 2003 − June 2018). The impact of these psychological comorbidities on QoL and economic burd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 105 publications
(238 reference statements)
1
36
2
2
Order By: Relevance
“…In its active state, IBD manifests with symptoms of abdominal pain, weight loss, diarrhoea and rectal bleeding, which may result in reduced quality of life, social functioning and mental well‐being 5 . Conversely, individuals with IBD who suffer from depression and anxiety are more likely to have adverse IBD outcomes and increased contact with healthcare providers 6‐8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In its active state, IBD manifests with symptoms of abdominal pain, weight loss, diarrhoea and rectal bleeding, which may result in reduced quality of life, social functioning and mental well‐being 5 . Conversely, individuals with IBD who suffer from depression and anxiety are more likely to have adverse IBD outcomes and increased contact with healthcare providers 6‐8 …”
Section: Introductionmentioning
confidence: 99%
“…5 Conversely, individuals with IBD who suffer from depression and anxiety are more likely to have adverse IBD outcomes and increased contact with healthcare providers. [6][7][8] Depression and anxiety are the most common comorbid psychiatric disorders diagnosed amongst individuals with IBD. 4 Antidepressant medications (ADM) are most frequently used to treat these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous work [ 26 , 94 – 96 ], it is likely these involve glia (astrocytes and/or microglia) and alterations in hippocampal neurogenesis. Nevertheless, given the frequent association of maladaptive behavioral changes, including anxiety, in IBD patients [ 6 , 7 , 9 ], our new observations suggest that this leukocyte–cerebral endothelium–IL-1β axis may represent an opportunity to develop novel targets for treating IBD-associated behavioral alterations.…”
Section: Discussionmentioning
confidence: 99%
“…The current study extends the literature by demonstrating the efficacy of an online MBI for people with IBD, a population at risk for depression ( Mittermaier et al, 2004 ; Graff et al, 2009 ). A systematic review found that people with comorbid anxiety and depression in IBD could benefit from non-pharmacologic interventions, yet often did not have access to interventions ( Dubinsky et al, 2021 ). In a longitudinal study, Jordi et al (2021) found that depression at enrollment was a robust risk factor for more severe IBD disease and inflammatory activity over time.…”
Section: Discussionmentioning
confidence: 99%